Evaluasi Kinerja Karyawan dengan Graphic Rating Scales di Departemen Maintenance PT Golden Living Indonesia - Kasim Kasim; Syamsul Hidayat (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to analyze the performance evaluation of four employees of the Maintenance Department of PT Golden Living Indonesia using the Graphic Rating Scale (GRS) model in a quantitative descriptive manner. The data used are the results of employee performance evaluations (scores 1–5) that are already available and documented by the company. This research approach is quantitative with descriptive analysis, calculating the average score, score range, and performance category of each employee based on predetermined criteria. The results show that the average employee performance score is 4.085 (scale 1–5), which is classified in the Good category. All four employees obtained a final result in the category “B” (Good), with a score range between 3.94 to 4.23. These findings indicate that employee performance is relatively consistent and meets organizational expectations. The application of the GRS model is considered effective in providing a clear, simple, and measurable overview of individual performance, and it can be used as a basis for managerial decision-making and future performance improvement efforts.